Energy Box Simulator - Fitriyah, Qoriatul; Sebayang, Irma Sherina; Nugroho, Berto Yusuf; Setyawan, Albertus Agung Danatyo; Wahyudi, Muhammad Prihadi Eko (JURNAL INTEGRASI, 2024)
This research is focused on making the trainer kit in the form of a device for measuring and calculating energy with an interactive practicum mode that is fun for students as part of the Thermodynamics course. This device will be equipped with a timer for measuring time, electrical mass measurement and a length calculator for measuring kinetic energy and potential energy using data on mass, velocity and height of an object. The data obtained from the measurement results will then be compared with the results of calculations on an application-based simulator in the visual basic .exe program.